2017
DOI: 10.1039/c7bm00061h
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field application or mechanical stimulation via magnetic microparticles does not enhance chondrogenesis in mesenchymal stem cell sheets

Abstract: Using a novel magnetic field bioreactor, this work evaluated the chondrogenesis of scaffold-free human mesenchymal stem cell sheets in response to static and variable magnetic fields, as well as mechanical stimulation via 4.4 µm magnetic particles. Neither static nor variable magnetic fields generated by 1.44 – 1.45 T permanent magnets affected cartilage formation. Notably, magnetic field-induced mechanical stimulation by magnetic particles, which applied forces to the cells and ECM statically (4.39 pN) or cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…This suggests an unlikely efficient interaction between magnetic fields and cells. Dikina, Lai, Cao, Zborowski, and Alsberg's () findings revealed no magnetic field‐induced effects on cartilage formation in hMSC sheets stimulated with static and variable magnetic fields. According to Fioravanti, Nerucci, Collodel, Markoll, and Marcolongo (), one should also consider the magnetic to electric transduction in cells as the magnetic effects on the ions and the ion channels ultimately gives rise to a transmembrane voltage potential.…”
Section: Discussionmentioning
confidence: 92%
“…This suggests an unlikely efficient interaction between magnetic fields and cells. Dikina, Lai, Cao, Zborowski, and Alsberg's () findings revealed no magnetic field‐induced effects on cartilage formation in hMSC sheets stimulated with static and variable magnetic fields. According to Fioravanti, Nerucci, Collodel, Markoll, and Marcolongo (), one should also consider the magnetic to electric transduction in cells as the magnetic effects on the ions and the ion channels ultimately gives rise to a transmembrane voltage potential.…”
Section: Discussionmentioning
confidence: 92%
“…There is not currently a consensus on the effect of static or alternating magnetic fields on cells. [61][62][63][64] Here, cells on non-actuated control devices were exposed to a static magnetic field from the embedded permanent magnet, but were not exposed to the time-varying magnetic field. Although we do not anticipate that the static or dynamic magnetic fields will affect breast cancer cell behavior, this is worth investigating in future studies which aim to more deeply explore the metabolic activity, matrix deposition, and mechanotransduction of metastatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that magnetic fields affect cells, tissues, and entire organisms, including the formation of the extracellular matrix of hyaline cartilage, proliferation of bovine chondrocytes, and the synthesis of proteoglycan [ 29 , 30 ]. Magnetic field bioreactors are advantageous, because they can meet the requirement of sterile culture conditions by contactless culture [ 31 , 32 ]. Most of them consist of one or a group of permanent magnets that influence the behavior of cells through static or dynamic magnetic field strengths ( Figure 1(d) ).…”
Section: Common Types Of Bioreactorsmentioning
confidence: 99%
“…In another study, however, Dikina et al investigated a variable magnetic field bioreactor composed of permanent magnets that were used for the culture of scaffold-free, high-density hMSC sheets, and the results showed that the bioreactor did not enhance chondrogenesis in the cell-only sheets. Therefore, more studies should be performed to validate the enhanced ability of chondrogenesis in response to magnetic fields [ 31 ].…”
Section: Common Types Of Bioreactorsmentioning
confidence: 99%